Inducible High Resistance to Colistin in Proteus Strains - Shimizu, Shoji (1977)
Wild-type Proteus strains are usually resistant to colistin. We have observed an increase in the level of colistin resistance in four clinical isolates of P. vulgaris, P. morganii, and P. rettgeri by prior treatment with subinhibitory concentrations of the drug. The enhanced resistance in these strains was lost after cultivating them in colistin-free medium, indicating that the enhanced resistance in the Proteus group is inducible.